Analysis of Telecommunication Tower Accounting at PT. Sarana Menara Nusantara Tbk. in 2014-2015 period - Shinta Anggraeny; Trisna Oktavia; Sugiharto (Politeknik Negeri Madiun, 2020)
This study aims to determine the accounting treatment of telecommunication tower companies, especially PT Sarana Menara Nusantara Tbk, which recognized telecommunications tower as fixed assets in 2014 and recognized as investment properties in 2015 and the impact of their accounting for that period. This type of research is qualitative research, using interpretive descriptative methods. Data presented in descriptive form without processing with other analitycal techniques. With this research, information is expected to equalize perceptions related to differences that occur regarding differences in recognition of telecommunications tower and to assist companies in evaluating performance, especially in terms of achieving earning.